GIP-induced vasodilation in human adipose tissue involves capillary recruitment. Issue 6 (June 2019) - Asmar, Meena; Asmar, Ali; Simonsen, Lene; Dela, Flemming; Holst, Jens Juul; Bülow, Jens
Abstract : Glucose-dependent insulinotropic polypeptide (GIP) in combination with hyperinsulinemia increase blood flow and triglyceride clearance in subcutaneous abdominal adipose tissue in lean humans. The present experiments were performed to determine whether the increase involves capillary recruitment. Eight lean healthy volunteers were studied before and after 1 h infusion of GIP or saline during a hyperglycemic–hyperinsulinemic clamp, raising plasma glucose and insulin to postprandial levels. Subcutaneous abdominal adipose tissue blood flow (ATBF) was measured by the 133 Xenon clearance technique, and microvascular blood volume was determined by contrast-enhanced ultrasound imaging. During infusion of saline and the clamp, both ATBF (2.7 ± 0.5 mL/min 100 g/tissue) and microvascular blood volume remained unchanged throughout the experiments. During GIP infusion and the clamp, ATBF increased fourfold to 11.4 ± 1.9 mL/min 100 g/tissue, P < 0.001. Likewise, the contrast-enhanced ultrasound signal intensity, a measure of the microvascular blood volume, increased significantly 1 h after infusion of GIP and the clamp ( P = 0.003), but not in the control experiments. In conclusion, the increase in ATBF during GIP infusion involves recruitment of capillaries in healthy lean subjects, which probably increases the interaction of circulating lipoproteins with lipoprotein lipase, thus promoting adipose tissue lipid uptake.